2018
DOI: 10.1186/s12992-018-0410-5
|View full text |Cite
|
Sign up to set email alerts
|

Using concept mapping to develop a human rights based indicator framework to assess country efforts to strengthen rehabilitation provision and policy: the Rehabilitation System Diagnosis and Dialogue framework (RESYST)

Abstract: BackgroundRehabilitation is crucial for the realization of the right to health and a proper concern of global health. Yet, reliable information to guide rehabilitation service planning is unavailable in many countries in part due to the lack of appropriate indicators. To ensure universal health coverage and meet the central imperative of “leaving no one behind” countries must be able to assess key aspects of rehabilitation policy and provision and monitor how they have discharged their human rights responsibil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In the rehabilitation field, advancing HPSSR is an increasing priority. This has been evident through recent publications in scientific journals on the role for and value of advancing rehabilitation health-services research [10,11,[25][26][27], a number of empirical works, research syntheses and frameworks on rehabilitation health policy and health systems issues [12,[28][29][30], rehabilitation stakeholders or interest groups with a focus on advancing rehabilitation services and services research [31,32], funding mechanisms or funding policies welcoming HPSSR in the rehabilitation field [33,34], and the recent input from the World Health Organization for developing a rehabilitation health policy and health systems research agenda [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the rehabilitation field, advancing HPSSR is an increasing priority. This has been evident through recent publications in scientific journals on the role for and value of advancing rehabilitation health-services research [10,11,[25][26][27], a number of empirical works, research syntheses and frameworks on rehabilitation health policy and health systems issues [12,[28][29][30], rehabilitation stakeholders or interest groups with a focus on advancing rehabilitation services and services research [31,32], funding mechanisms or funding policies welcoming HPSSR in the rehabilitation field [33,34], and the recent input from the World Health Organization for developing a rehabilitation health policy and health systems research agenda [13].…”
Section: Introductionmentioning
confidence: 99%
“…34 Finally, local and global stakeholders' awareness has emerged only recently for the need to monitor, plan and develop rehabilitation resources, in tandem with the growing awareness of population ageing and the increasing rates of chronic conditions, disabilities, and corresponding physical rehabilitation needs. 3,14,20,[35][36][37][38] Within the 35 HICs, great disparities were found for the OTs and PTs supply per capita, eg, up to 40 times the difference. Our inferential analysis showed that such a disparity was not explained by varying need levels; the latter had a more sensible variation, eg, up to 2.5 times the difference.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-one new publications were identified, of which three described QIs or quality measures for different managements of rheumatoid arthritis and osteoarthritis [16], psoriatic arthritis [17] and inflammatory arthritis [18]. One paper described human rights based indicator framework systems to assess countries´ efforts to strengthen rehabilitation provision and policy [22].…”
Section: Methodsmentioning
confidence: 99%
“…However, most quality sets mainly include process indicators, some of them related to rehabilitation and some not, and the development processes were suboptimal [15, 18]. Comprehensive and resource demanding quality assurance and accreditation systems for social and rehabilitation services exist [19–21], as do human rights based indicator framework systems to assess countries´ efforts to strengthen rehabilitation provision and policy [22]. Nevertheless, to our knowledge, no valid and feasible indicator set has been developed for use in rehabilitation of RMDs, covering both structure, process and outcome quality and using appropriate methodology.…”
Section: Introductionmentioning
confidence: 99%